The Effect of Employee Conflict and Work Stress on Employee Performance at PT. ISS Indonesia in Cilandak - Juwita Ramadhani Fitria (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study was to determine the effect of work conflict and work stress on employee performance at PT. ISS Indonesia either partially or simultaneously. The method used is quantitative. The sampling technique used is saturated sampling and the sample obtained in this study amounted to 57 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The result of this study is that work conflict has a significant effect on employee performance with the regression equation Y = 55,469 + -0.657X1, the correlation value is -0.746, meaning that the two variables have a strong relationship. The value of the coefficient of determination is 55.6%. Hypothesis test obtained t count > t table or (7.305 > 2.002). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant effect of work conflict on employee performance. Work stress has a significant effect on employee performance with the regression equation Y = 51.997 + -0.561X2, the correlation value is -0.689, meaning that the two variables have a strong relationship. The value of the coefficient of determination is 47.5%. Hypothesis test obtained t arithmetic > t table or (7.957 > 2.002). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of work stress on employee performance. Work conflict and work stress have a significant effect on employee performance with the regression equation Y = 55.596 + -0.557X1 + -0.104X2. The correlation value is 0.748, meaning that the independent variable and the dependent variable have a strong relationship. The value of the coefficient of determination is 55.9% while the remaining 44.1% is influenced by other factors. Hypothesis test obtained value of F arithmetic > F table or (34.265 > 2.780). Thus, H0 is rejected and H3 is accepted. This means that there is a simultaneous significant effect of work conflict and work stress on employee performance.